How plants protect the flowers from unbidden guests - Dahl, Anna Magdalena (My University, 1898)
Introduction: As the result of the enormous increase in the numbers of individuals of almost every species, a constant struggle for existence has become the fate of nearly every organism, animal and vegetable. Thus, in order to withstand these struggles, and not lose the object of their competition; there has been developed in the different competitions, different features of their constitution In some, we find the perfecting powers of active attack; but in the plant world the most particular feature is the facility for active or passive defense. The aggressive movements of plants are prevented by their want of locomotion, and so in order to succeed in the struggle, they must be better adapted to environments than their competitors, or the individual must be guarded from other organisms inclined to prey upon it, by some protective mechanical mean.
Citation: Dahl, Anna Magdalena. How plants protect the flowers from unbidden guests. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Organism; Animal; Vegetable; Plant; Locomotion; Theses; Manuscripts (documents)